2017
DOI: 10.1038/srep40606
|View full text |Cite
|
Sign up to set email alerts
|

A computational psychiatry approach identifies how alpha-2A noradrenergic agonist Guanfacine affects feature-based reinforcement learning in the macaque

Abstract: Noradrenaline is believed to support cognitive flexibility through the alpha 2A noradrenergic receptor (a2A-NAR) acting in prefrontal cortex. Enhanced flexibility has been inferred from improved working memory with the a2A-NA agonist Guanfacine. But it has been unclear whether Guanfacine improves specific attention and learning mechanisms beyond working memory, and whether the drug effects can be formalized computationally to allow single subject predictions. We tested and confirmed these suggestions in a case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 67 publications
9
42
0
Order By: Relevance
“…norepinephrine receptors could be one route α7 could improve learning. Strong support for this scenario comes from a previous study in which we found a similar faster reversal learning performance at optimal doses of the α-2A noradrenergic agonist Guanfacine (Hassani SA et al 2017). In that study, an increased reversal learning speed was the most prominent behavioral effect during prolonged testing at effective doses.…”
Section: Nicotinic Sub-receptor Specific Modulation Of Learning and Asupporting
confidence: 71%
See 1 more Smart Citation
“…norepinephrine receptors could be one route α7 could improve learning. Strong support for this scenario comes from a previous study in which we found a similar faster reversal learning performance at optimal doses of the α-2A noradrenergic agonist Guanfacine (Hassani SA et al 2017). In that study, an increased reversal learning speed was the most prominent behavioral effect during prolonged testing at effective doses.…”
Section: Nicotinic Sub-receptor Specific Modulation Of Learning and Asupporting
confidence: 71%
“…we computed the learning curves for each reversal block using an ideal observer statistics that calculated how consistently the monkeys choices were rewarded across sequences of trials (see Methods, and (Hassani SA et al 2017)). We then fit the resulting learning curves with a hyperbolic ratio function to extract the trial number at which the learning reached 50% of the maximum asymptotic performance value, which could be early or late, corresponding to fast versus slow learning ( Fig.…”
Section: Effects Of Nachr Agonists On Feature-based Learningmentioning
confidence: 99%
“…Figure S1A, S3A, B). To discern trial-by-trial encoding of prediction errors we fitted an attention weighting reinforcement learning model to the choice data of the monkeys (Figure 1D, see Methods) (Hassani et al, 2017;Leong et al, 2017;Wilson and Niv, 2011). We then correlated the model derived reward prediction errors (RPEs) with the neural firing rates during the 0-1.5 sec.…”
Section: Behaviormentioning
confidence: 99%
“…Biasing attention to those features causing outcomes that have been most unexpected can optimize attentional sampling in the long run to those stimuli with the most reward-predictive features (Daddaoua et al, 2016;Dayan et al, 2000;Ghazizadeh et al, 2016). The mechanisms underlying this attentional optimization through reinforcement learning have been explored in recent studies suggesting that attentional guidance by prediction errors is facilitated when value predictions are already biased towards those feature dimensions that are most likely reward predictive (Hassani et al, 2017;Leong et al, 2017;Niv et al, 2015;Wilson and Niv, 2011). Instead of attending all possible feature dimensions of a stimulus equally, prioritizing those dimensions that most prominently are reward predictive dramatically enhances the learning speed (Farashahi et al, 2017;Kruschke and Hullinger, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The animals were engaged in an over-trained 130 attention tasks in which they would use saccadic eye movements to acquire juice reward (Fig S1). 131 The specifics of the task are described elsewhere (Hassani et al 2017). Both animals showed stable 132 performance and acquired similar reward volumes on all recording days.…”
Section: Methods 119mentioning
confidence: 99%